2014
DOI: 10.5539/jas.v6n6p176
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Growth of Shrimp Aquaculture Through Biofloc Production as Alternative to Fishmeal in Shrimp Feeds

Abstract: As capture fisheries are now fully exploited in Egypt, aquaculture is considered the only source for meeting the demand of seafood for rapidly growing populations in Egypt. To meet these demands for seafood, aquaculture has to grow fast and to be more intensive. Fishmeal sources from capture fisheries are fully exploited and thus become costly ingredient in fish and crustacean feed formulations. The present study evaluated biofloc technology as a sustainable alternative to fishmeal in the shrimp feeds using ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 60 publications
(72 reference statements)
4
23
0
Order By: Relevance
“…Survival of the control and Barley flour treatments was highest than in the other treatments. This results are in agreement with numerous studies have reported enhanced survival, health, and growth rates of shrimp raised in ponds with high activity of algae, microbial flocs, and other natural biota (Cuzon et al, 2004;and Wasielesky et al, 2006;Mohamed 2014 andMegahed et al, 2018).…”
Section: Growth Performance and Feed Utilizationsupporting
confidence: 93%
See 1 more Smart Citation
“…Survival of the control and Barley flour treatments was highest than in the other treatments. This results are in agreement with numerous studies have reported enhanced survival, health, and growth rates of shrimp raised in ponds with high activity of algae, microbial flocs, and other natural biota (Cuzon et al, 2004;and Wasielesky et al, 2006;Mohamed 2014 andMegahed et al, 2018).…”
Section: Growth Performance and Feed Utilizationsupporting
confidence: 93%
“…Starvation, which was caused by the poor feed accessibility, likely triggered the cannibalistic behavior of the shrimp (FAO, 2003). Application of carbohydrate improves growth rate in F. indicus (Megahed and Mohamed, 2014;Megahed et al, 2018) L. vannamei (Serra et al, 2015) and in P. monodon (Anand, et al, 2017) and Biofloc used as a natural food for the cultured shrimp (Burford et al, 2004) apart from being a source of bioactive compounds and growth promoters (Ju et al, 2008;Megahed and Mohamed, 2014;Megahed et al,2018). Moreover, digestive enzyme secretions from many probiotic bacteria like Bacillus, Lactobacillus in the carbohydrate added groups might have improved the shrimp growth performance (Ringo, et al, 2012;Anand et al, 2014;Megahed and Mohamed, 2014;Megahed et al 2018).…”
Section: Growth Performance and Feed Utilizationmentioning
confidence: 99%
“…A balanced diet produced by the biofloc system can be used as alternative feed in marine shrimp farming to reduce dependence on fish meal and fish oil in nutrition (Megahed & Mohamed, ). Studies have been proven that shrimp culture in a biofloc system increases growth to 15% and decreases feed conversion ratio to 40% (Wasielesky, Atwood, Stokes, & Browdy, ; Xu & Pan, , ).…”
Section: Introductionmentioning
confidence: 99%
“…A balanced diet produced by the biofloc system can be used as alternative feed in marine shrimp farming to reduce dependence on fish meal and fish oil in nutrition (Megahed & Mohamed, 2014).…”
mentioning
confidence: 99%
“…The use of microbial biofilms and bioflocs as direct food sources has exhibited a vigorous growth accompanied by successful results over the last decade (De Schryver et al 2008;Crab et al 2012;Megahed & Mohamed 2014;Mart ınez-C ordova et al 2015). For example, yield production of fish and shrimp can be doubled when bioflocs are combined with formulated feed because they are a rapidgrowing source of not only protein but also vitamins and lipids (depending on their composition) (Kuhn et al 2009;Emerenciano et al 2012).…”
Section: Microbial Communities Forming Bioflocsmentioning
confidence: 99%